Ezra Dunkle-Polier as William Blore, Emma Holliday as Doctor Armstrong, Thomas Martinez as Philip Lombard, and Katherine Sawyer as Vera Claythorne in 'And Then There Were None' (Tufts Archival Research Center, 2008)
Directed by Katie Welch. Production date was 2009-11-09.